Decision Making in Radiation Oncology Volume 2 - Lu, Jiade J.; Brady, Luther W.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
Decision Making in Radiation Oncology is a reference book designed to enable radiation oncologists, including those in training, to make diagnostic and treatment decisions effectively and efficiently.    The orientation of this groundbreaking publication is entirely practical, in that the focus is on issues relating to cancer management. The design has been carefully chosen based on the belief that “a picture is worth a thousand words”:  Knowledge is conveyed through an illustrative approach using algorithms, schemas, graphics, and tables. Text is kept to a minimum, reducing the effort involved in reading while enhancing understanding.   Detailed guidelines are provided for multidisciplinary cancer management as well as for radiation therapy techniques.  In addition to the attention-riveting algorithms for diagnosis and treatment, strategies for the management of disease at individual stages are detailed for all the commonly diagnosed malignancies. Detailed attention is given to the core evidence that has shaped the current treatment standards and advanced radiation therapy techniques. Clinical trials that have yielded “gold standard” treatment and their results are documented in the schemas. Moreover, radiation techniques, including treatment planning and delivery, are also presented in an illustrative way.
Volume 1: Introduction -- Section I: Head and Neck Cancers: Orbital and Ocular Malignancies -- Nasopharyngeal Carcinoma -- Cancer of Oral Cavity and Oropharynx -- Malignant Tumors of the Major Salivary Glands -- Cancer of Larynx and Hypopharynx -- Squamous Cell Carcinoma of Unknown Head and Neck Primary -- Thyroid Cancer -- Section II: Breast Cancer: Breast Cancer -- Section III: Tumors of the Thorax: Lung Cancer (NSCLC & SCLC) -- Thymoma -- Esophageal Cancer -- Section IV: Cancers of the Gastrointestinal Tract: Gastric Cancer.-Pancreatic Cancer -- Hepatobiliary Tumors -- Rectal Cancer -- Cancer of the Anal Canal. Volume 2: Section V: Tumors of the Genitalurinary System: Cancer of the Bladder -- Cancer of the Prostate -- Testicular Cancer -- Section VI: Gynaecological Cancers: Endometrial Cancer.-Cancer of the Cervix -- Vulva Cancer -- Vaginal Cancer -- Section VII: Lymphomas: Non-Hodgkin’s Lymphoma -- Hodgkin’s Disease -- Multiple Myeloma and Plasmacytoma.-Cutaneous T-Cell Lymphoma -- CNS Lymphoma -- Section VIII: Tumors of the Central Nervous System: Meningioma -- Adult Glioma -- Pituitary Tumors -- Section IX: Skin Cancers and Soft Tissue Sarcoma: Skin Cancers including Melanoma -- Soft Tissue Sarcoma -- Section X: Pediatric Tumors: Pediatric CNS Tumors -- Retinoblastoma -- Neuroblastoma -- Ewing’s Sarcoma -- Wilm’s Tumor -- Section XI: Other: Palliative Radiation for Brain Metastasis -- Palliative Radiation for Bone Metastasis -- Appendix I: TD 5/5 (table) -- Appendix II: Performance Status Scales -- Subject Index.
Keywords: Radiology; Radiotherapy; Oncology .; Imaging / Radiology; Radiotherapy; Oncology